Asking Questions The Sandler Way - Garrido, Antonio (Ascent Audio, 2020)
When does the sales process really begin? Some say that sales starts at the very first "hello." Everything before that first critical opening word, these people say, is marketing; everything after that is sales. Others say that the real work of sales doesn't begin till the prospect first says, "No." "Otherwise," they insist, "it's just order-taking." Antonio Garrido's Asking Questions the Sandler Way rejects both of those answers. It holds that selling begins when you start asking good questions. This book is about asking the right questions, so that both the seller and the buyer discover the right solution as efficiently and as effectively as possible-even if they discover that the right solution right now is for the prospect to buy from the competition. Although that may be an unconventional selling standard, it's a powerful and extremely effective one. This book is about not looking, sounding, or thinking like the average salesperson. It's about keeping barriers down and communication lines open. It's about getting to the right solution, faster, more efficiently, and with less stress. It's about asking the right questions, in the right way, at the right time, for the right reason. It's about asking questions the Sandler way.